2022
DOI: 10.1177/09544089221093306
|View full text |Cite
|
Sign up to set email alerts
|

The incremental sheet forming; technology, modeling and formability: A brief review

Abstract: The constant need to improve manufacturing processes and production methods, with the aim of making these processes more flexible and precise, and subsequently solving problems of conformity, quality of manufactured parts and productivity, drives manufacturers to develop original manufacturing techniques. The incremental sheet metal forming process, one of these novel techniques, has attracted a great deal of attention in recent decades. This paper presents a review of recent work done in this area and capture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 118 publications
0
7
0
Order By: Relevance
“…Thus, SPIF has greater potential in the aspects of rapid prototype manufacturing as well as small batch production [1,2]. SPIF can fulfil the current requirements for flexible, feasible, sustainable, and economic manufacturing technology for personalized sheet metal parts, small-batch prototypes, and customized products without the use of expensive specialized machines or equipment [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, SPIF has greater potential in the aspects of rapid prototype manufacturing as well as small batch production [1,2]. SPIF can fulfil the current requirements for flexible, feasible, sustainable, and economic manufacturing technology for personalized sheet metal parts, small-batch prototypes, and customized products without the use of expensive specialized machines or equipment [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it was found that by moving a punch along a programmed trajectory, parts of complex configuration could be obtained. A presentation of the process as well as the technological variants of formability in SPIF has been provided by Ben Said [ 1 ]. A study on the influence of the process parameters in SPIF is provided by Magdum and Chinnaiyan [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional forming processes, SPIF deforms the material under severe plastic strain as a result of local deformation and throughthickness shearing. SPIF is particularly suitable for the rapid making of prototype products and components in small quantities with high demand on geometry accuracy [1][2][3][4][5]. For example, recent reports on the making of Al-Cu alloy truncated pyramid component by SPIF have attracted a lot attention due to its advantages on improving geometry accuracy [6].…”
Section: Introductionmentioning
confidence: 99%